Oxidation Behavior of Zr-1Nb Corroded in Air at 400 °C after Plasma Immersion Titanium Implantation - Obrosov A. Aleksey; Sutygina A. N. Alina Nikolaevna; Manakhov A. M. Anton Mikhaylovich; Bolz S. Sebastian; Weifs S. Sabine; Kashkarov E. B. Egor Borisovich (2018, 2018)
Title screen